Citogenética comparativa e DNA barcode em Astyanax lacustris Lütken, 1875 Astyanax abramis Jenyns, 1842 e Astyanax pirapuan Tagliacollo, Britzke, Silva & Benine, 2011 (Characiformes, Characidae) da Bacia do Alto Paraguai - Silva, Thais Kelly Souza Teixeira da (2016)
Cytogenetic analysis in Astyanax showed that the genus has a great variability related to chromosome numbers, quantity and positioning of rDNA sites, and other markers used in cytogenetic characterization of these species, and somehow corroborate the taxonomy andthe existence of a species complex. In addition to the cytogenetic data, a modern approach has been used to the characterization and identification of species through a fragment of the mitochondrial genome (mtDNA) - Cytochrome Oxidase Subunit I (COI). Therefore, in order to increase the cytogenetic information of the genus Astyanax and produce data which can support future taxonomic studies, this paper addresses, integrative analysis including cytogenetic, morphological and molecular data, of three species of Astyanax belonging to the basin of upper Paraguay, two of these species considered cryptic, here reported in syntopy (A. lacustris and A. Abramis) belonging to "A. bimaculatus complex" and the first cytogenetic description of A. pirapuan. For the identification of cryptic species we used lateral line scales count and performed cytogenetic characterization and rDNA mapping beyond the sequencing of COI gene of the three species. The unique character of morphological differentiation between A. lacustris and A. abramis is the scales count on the sideline which is not possible to distinguish them. Cytogenetic analysis revealed 2n = 50 chromosomes for all species difference in karyotype morphology of each, where A. lacustris presented 6m + 10sm + 18st + 16a and NF = 84, A. Abramis 8m + 10sm + 26st + 6a and NF = 94 and A. pirapuan 6m + 14sm + 14st + 16a and NF = 96. Only A. pirapuan presented AgNOR system with multiple sites detected with silver nitrate, and confirmed with the mapping of 18S rDNA. For the 5S rDNA sites, A. lacustris presented two sites, six sites in A. abramis and four sites markings in A. pirapuan. The COI analysis confirm the existence of two distinct lineages, in addition to a possible differentiation between populations of Astyanax pirapuan based on molecular markers and cytogenetics, which seems to be a reflection of a population structure that needs to be better understood, demonstrating the importance of integration of chromosomal, genetic and molecular data for better diagnosis in Astyanax.